WORD FORMATION OF “STONKS MEMES” ON THE INTERNET - Kaka Ary Sobarna; Abdul Hannan (CALL, 2022)
The word formation process is concerned with how new words are produced, whether through the modification of preexisting terms or through total invention, which later becomes a component of the "Stonks Memes" language used on the internet. The two goals of this study are as follows: the first is to identify the slang term's altered meaning in "Stonks Memes," and the second is to highlight the process modifications and changes that appear in the online varieties of "Stonks Memes." This method, which classified data based on morphology theory and used Yule's theory as the primary one for analyzing word formation and morphological system, was descriptive in nature. The word-formation process occurred because of the necessity of the stonk meme format, which required the term to be transformed to convey a hilarious connotation. This study found four forms of word-formation processes, including back-formation, coinage, borrowing, and blending. It is concluded that the word in question was purposely altered by the meme developer to fit in the stonk memes framework, changing both the word's sound and its meaning.Keywords: word-formation process, slang, memes, stonks, internet